PERANCANGAN UI/UX APLIKASI KESEHATAN PATIENT-CENTRIC MENGGUNAKAN METODE USER CENTERED DESIGN BERBASIS MOBILE (STUDI KASUS: KLINIK MUHAMMADIYAH) - fadel, FadelMuhammad; Kusnadi, Kusnadi; Fahrudin, Rifqi (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2025)
The rapid development of digital technology in the healthcare sector has encouraged clinics and healthcare facilities to improve service quality through application-based innovations. Klinik Muhammadiyah, as one of the healthcare providers, seeks to adopt a patient-centric healthcare application designed to facilitate patients in accessing information, registering for services, and interacting with medical professionals. This study aims to design the user interface (UI) and user experience (UX) of a patient-centric healthcare application by applying the User-Centered Design (UCD) method. The UCD approach was chosen because it emphasizes active user involvement at every stage of the development process, from needs analysis, design, to evaluation. Data collection was conducted through interviews, questionnaires, and observations involving patients, medical staff, and administrative personnel. The design results were visualized in the form of wireframes and high-fidelity prototypes, which were then evaluated using usability testing with parameters of effectiveness, efficiency, and satisfaction. The evaluation results show that the developed UI/UX design meets user needs and provides a more intuitive, faster, and satisfactory user experience. Therefore, the application of the UCD method proves to be effective in designing a patient-centric healthcare application that can enhance service quality at Klinik Muhammadiyah. Keywords: User-Centered Design, UI/UX, Healthcare Application, Patient-Centric, Klinik Muhammadiyah